Dyskusja nad tezą o wzroście narcyzmu we współczesnych społeczeństwach - Barbara Gawda, Barbara Gawda (Człowiek i Społeczeństwo, 2018)
The article aims to discuss the thesis on ‘narcissistic epidemic’ that was highlighted in publications from culture and social studies. The different ways of defining of narcissism, different concepts of narcissism, psychological characteristic of people displaying narcissism, and research focused on its description will be analyzed. To illustrate the famous thesis on ‘narcissistic epidemic’ in the modern world the data on the prevalence of narcissistic personality disorder in many countries, including Poland, will be discussed. The documented not too high prevalence of narcissistic personality disorder in high-income countries from the world seems to be stable. It means that the thesis on increasing level of narcissism in capitalist countries was not supported by the research from psychopathology.